2018
DOI: 10.1002/pc.24949
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the concentration of copper nanoparticles on the thermo‐mechanical and antibacterial properties of nanocomposites based on poly(butylene adipate‐co‐terephthalate)

Abstract: Poly(butylene adipate‐co‐terephthalate) (PBAT) was mixed with copper nanoparticles (Cu‐NPs) in concentrations of 1%, 3%, and 5% with particle size between 100 nm and 200 nm by the melting method. A morphological, thermal, and structural characterization of the nanocomposites (NCs‐PBAT/Cu) was performed to analyze the effect of the Cu‐NPs on the polymer chains, as well as to explain the influence on their crystallinity, and its influence on the thermomechanical and antibacterial properties. The percentage of cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The OC improved the films' elasticity due to the digested organic molecules, such as proteins, carbohydrates, oils, and other molecules that are even aggregated in powder particles, which can interact with the PLA phase, improving the mechanical resistance 21,22 . The literature commonly reports that PBAT composites with natural compounds have low compatibility due to the polarity difference 23,24 . The use of blends with PLA was beneficial in the present work, increasing the matrix‐reinforcement interactions, reflecting in increases in tension and a slight decrease in the composite's stiffness.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…The OC improved the films' elasticity due to the digested organic molecules, such as proteins, carbohydrates, oils, and other molecules that are even aggregated in powder particles, which can interact with the PLA phase, improving the mechanical resistance 21,22 . The literature commonly reports that PBAT composites with natural compounds have low compatibility due to the polarity difference 23,24 . The use of blends with PLA was beneficial in the present work, increasing the matrix‐reinforcement interactions, reflecting in increases in tension and a slight decrease in the composite's stiffness.…”
Section: Resultsmentioning
confidence: 71%
“…21,22 The literature commonly reports that PBAT composites with natural compounds have low compatibility due to the polarity difference. 23,24 The use of blends with PLA was beneficial in the present work, increasing the matrixreinforcement interactions, reflecting in increases in tension and a slight decrease in the composite's stiffness. Similar results were obtained for C3, with an increase in the rigidity (E = 37 MPa) and a significant decrease in the composites' ductility (ε = 110%) after the RHs addition.…”
Section: Mechanical Propertiesmentioning
confidence: 80%
“…The NP content caused a decrease in the OTR and WVTR values, indicating that the PBAT/P(MMA- co -MA)–SiO 2 ternary composites have good barrier properties. Previous studies reported activities in the OTR and WVTR for SiO 2 -reinforced PBAT [ 58 ]. Water and oxygen molecules can travel through PBAT films completely free of impurities.…”
Section: Resultsmentioning
confidence: 99%
“…that the E content of PBAT films decreased when the content of Cu nanoparticles in the PBAT matrix increased (Felipe Jaramillo et al, 2019). And nano silver oxide which agglomerated in PBAT matrix would also reduce the mechanical properties of the nanocomposite films .…”
Section: Mechanical Propertiesmentioning
confidence: 97%